Making a mint : comparative studies in Late Iron Age coin mould - Landon, Mark (Archaeopress Archaeology, 2016)
This book presents the first large-scale comparative study of Iron Age coin mould. The subject of Iron Age minting techniques is an important one that reveals a great deal about Iron Age political organisation and economy but which, until now, has remained largely unreported. In addition to examining in detail approximately 20% of all the coin mould ever found, the book also addresses the lack of an agreed reporting protocol, the main and considerable obstacle to progress in this field. In addition to the detailed interpretation of all mould studied the volume also serves as a field guide to best practice in dealing with new material and finds.